Characterization of health-related quality of life based on the EQ-5D-5L questionnaire in head-and-neck cancer patients undergoing modern radiotherapy. (1st November 2020) - Sprave, Tanja; Zamboglou, Constantinos; Verma, Vivek; Nicolay, Nils H.; Grosu, Anca-Ligia; Lindenmeier, Jörg; Tscheulin, Dieter K.
ABSTRACT: Background : Patient-reported quality of life in cancer patients is becoming increasingly important, especially for head-and-neck (H&N) cancers, which are at risk of experiencing severe treatment-related toxicities. Therefore, we sought to characterize the peritherapeutic HRQOL of contemporary patients using the well-validated EQ-5D-5 L questionnaire. Methods : All patients receiving radiotherapy for H&N cancers between July 2019 and November 2019 at the University of Freiburg Medical Center who completed the first two follow-ups were included. Results : All 49 patients completed the questionnaires at all time points of data collection, yielding 196 total questionnaires. The mean EQ-5D-5 L index score of the overall population before radiotherapy, after radiotherapy, and three and six months following radiotherapy was 0.837 (standard deviation, SD 0.17), 0.828 (SD 0.16), 0.855 (SD 0.15), and 0.856 (SD 0.14) respectively. The respective mean EQ VAS scores were 63.88 (SD 20.72), 63.67 (SD 21.81), 63.67 (SD 21.81), and 65.20 (SD 22.41) respectively. The respective changes of the HI and EQ VAS score over time for this cohort were not significant (Friedman test p = 0.273, p = 0.618). Conclusion : Despite the known therapy-related toxicities, no significant permanent deterioration of HRQOL in this cohort was observed.